PRODUKSI DAN KEUNTUNGAN HASIL USAHATANI SEMANGKA (Citrullus vulgaris SCARD) DI DESA TELAGA KECAMATAN PELAIHARI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Bahrun; Ahmad Baparki (Fakultas Pertanian UVAYA Banjarmasin, 2020)
This study aims to determine technically the implementation of watermelon farming, economically regarding the costs, revenues, and profits of watermelon farming during one production process. This thesis research was carried out in Telaga Village, Pelaihari District,Tanah Laut Regency, South Kalimantan Province. Production obtained from watermelon farming in Telaga Village is an average of 12,942.57 kg/farmer or 11.30 tons/farmer. The average total revenue is Rp. 15,531,084,00/farmer. Average income is Rp. 9,564,436.92/farmer..The average profit is Rp. 7,754,562.80/farmer